COMBATE AO NEGACIONISMO CIENTÍFICO E ÀS FAKE NEWS NA PERSPECTIVA DOS PROFESSORES DE BIOLOGIA NA ESCOLA CENTRO EDUCA MAIS ALMIRANTE TAMANDARÉ - GONÇALVES, Marcia Amelia Gaspar Matos (2023)
This research deals with the topic of combating scientific denialism and fake news. The objective of the research was to investigate the possibilities of combating scientific denialism and fake news from the perspective of Biology teachers at Escola Centro Educa Mais Almirante Tamandaré, with a view to producing a digital Guide with pedagogical proposals that can contribute to combating untruths and the denial of science in the school environment and outside it. It is a research with a qualitative approach, classified in nature as applied and as participatory research. The research participants were four teachers who teach the High School Biology subject at the researched school, in the city of São Luís-MA. Semi-structured interviews were used as a data collection instrument. The interviews were carried out in person. The research data was analyzed from the perspective of Bardin's Content Analysis (2016). Five categories were created: Conceptions about scientific denialism; Conceptions about fake news; Combat strategies; Clarification and scientific foundation and encouragement of critical thinking. At the end of this exploratory research and with the analysis of the categories, it was evident that the teachers participating in the research have a defined conception of what scientific denialism and fake news are, configuring them as denying science and fake news to obtain some harm, respectively. . Regarding pedagogical combat strategies, teachers considered it very important to have them, but not everyone addresses this in the classroom. It was found that both denialism and fake news corroborate students' misinformation and that topics about vaccines and evolution were the most cited by teachers as those that suffer most from scientific denialism and fake news. We also note that the use of materials with scientific support is necessary in this fight and that encouraging the propagation of scientific truth with clarifications and justifications is extremely important according to those researched and that scientific truth reaffirms and implements the principles of science. Media and Information Literacy (AMI) stood out as one of the alternatives to achieve the objectives of this research, as AMI helps to develop in students the ability to analyze information in a critical way and to be prepared for this world of media and technology. We hope that the pedagogical proposal in the form of a digital Guide can contribute to the fight against scientific denialism and fake news, in the sense of enabling teachers to mediate, helping their students to reflect critically on the information they receive on Biology subjects.